Public spending and green economic growth in BRI region: Mediating role of green finance - Zhang, Dongyang; Mohsin, Muhammad; Rasheed, Abdul Khaliq; Chang, Youngho; Taghizadeh-Hesary, Farhad (Energy policy, 2021)
Generally, public spending on education, research, and development (R&D) is perceived to impact the economy and sustainability positively; however, such notion lacks evidence, particularly in Belt and Road Initiative (BRI) member countries. In this study, panel data of BRI member countries from 2008 to 2018 is analysed using the generalized method of moments (GMM) method and data envelopement analysis (DEA) to assess the relationship between public spending on R&D and green economic growth and energy efficiency. The study found a fluctuating green economic growth indicator during the research period attributed to the non-serious nature of government policies. The findings reveal that the GMM method confirms both composition and technique effects in the entire sample. Nonetheless, the result of the sub-sample showed a heterogeneous effect on high GDP per capita countries. Moreover, the study shows that public spending on human resources and R&D of green energy technologies prompts a sustainable green economy through labour and technology-oriented production activities and different effects in different countries. •Generalized method of moments used to assess the determinants of green growth.•The non-serious nature of government policies fluctuates the green growth indicators.•Public green finance promotes green economic growth.•Spending on human resources and R&D of green technologies promotes green growth.•The proliferation of human resource and innovations are essential to green growth.